Spinel NiAl2O4 Based Catalysts: Past, Present and Future - Yu, Xinmiao; Wang, Shifa; Gao, Huajing (Journal of Environmental Science and Engineering Technology, 2023)
Nickel aluminate (NiAl2O4) is a kind of partially antispinel structure oxide. Because of its excellent electronic structure and energy level structure, high thermal stability and high charge transfer and separation efficiency, it has a potential application prospect in catalytic oxidation, photocatalysis, adsorption and other fields. In this paper, the synthesis methods of different NiAl2O4-based catalysts, their applications in catalytic field and related catalytic mechanisms are reviewed from the appearance of single component NiAl2O4, ion-doped NiAl2O4 and multiheterojunction NiAl2O4 catalysts. The application of NiAl2O4 photocatalysts in the field of photocatalysis has gradually shifted from the degradation of dyes to the degradation of drugs, so its photocatalytic mechanism and degradation path need to be further studied. This review points out the direction for the future research of NiAl2O4 based catalysts in the field of catalysis.